The arrival of critical citizens: decline of political trust and shifting public priorities in China. Issue 1 (2nd January 2016) - Wang, Zhengxu; You, Yu
ABSTRACT: Political trust has been in decline in China. In this article, we capture this decline as reflecting the modernization of Chinese political culture. While the government managed to deliver a sustained period of rapid economic growth, the public's trust in it is diminishing through two mechanisms. On the one hand, Chinese citizens are acquiring stronger liberal democratic values, which make citizens more critical toward government institutions. On the other hand, changing political culture is also shown in the citizens' shifting of their priorities toward the expansion of freedom and empowerment of citizens. Decades of socioeconomic modernization, therefore, meant that the era of critical citizens has arrived in China.